Calcium responses in subserosal interstitial cells of the guinea‐pig proximal colon. Issue 1 (8th October 2013) - Tamada, H.; Hashitani, H.
Abstract Background In the subserosal layer between the longitudinal muscle layer and mesothelium, heterogeneous populations of interstitial cells are distributed. As the distribution of nerve elements in this layer is sparse as compared with the nerve plexus layer or tunica muscularis, there may be unique communication among subserosal interstitial cells (SSICs). This study aimed to explore functional properties of SSICs. Methods In subserosal preparations of the guinea‐pig proximal colon, changes in intracellular Ca2+ ([Ca2+]i) were visualized using Fluo‐4 Ca2+ imaging. Immunohistochemistry was also performed to identify the SSICs exhibiting Ca2+ transients. Key Results A majority of SSICs responded to adenosine triphosphate (ATP, 10 μM) by increasing [Ca2+]i, but remained quiescent during the application of acetylcholine (10 μM). ATP‐induced Ca2+ responses were mimicked by adenosine 5′‐diphosphate (10 μM), MRS2365 (10 nM) but not α, β‐methylene ATP (10 μM) or uridine triphosphate (10 μM), and could be reproduced in Ca2+‐free solution, suggesting that ATP acts via P2Y receptors, most likely P2Y1 subtype, but not P2X receptors. Live staining of the same preparations after Ca2+ imaging indicated the ATP‐sensitive SSICs were not positive for c‐Kit antibody, a specific marker for gastrointestinal interstitial cells of Cajal (ICC). Immunohistochemistry identified vimentin (mesenchymal cell marker)+/Kit‐ and SK3 (fibroblast‐like cell (FLC) marker)+/Kit‐ cells that had a similar morphology to the ATP‐sensitive SSICs in Ca2+ imaging. Conclusions & Inferences A majority of the SSICs in the guinea‐pig proximal colon, presumably FLC, are capable of responding to ATP and thus may contribute to smooth muscle relaxation upon stimulation with ATP released from non‐neuronal cells.